Probiotics as Antioxidant Strategy for Managing Diabetes Mellitus and Its Complications - Max Denisson Maurício Viana; Sthefane Silva Santos; Anna Beatriz Oliveira Cruz; Maria Vitória Abreu Cardoso de Jesus; Pedro Santana Sales Lauria; Marvin Paulo Lins; Cristiane Flora Villarreal (Antioxidants, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by impaired glycemic regulation and persistent hyperglycemia, which drives the onset of microvascular complications such as diabetic neuropathy and nephropathy. Chronic hyperglycemia activates oxidative stress pathways and alters gut microbiota composition, both of which contribute to disease progression. In this context, probiotics have emerged as promising therapeutic agents due to their ability to modulate oxidative stress, improve glycemic control, and influence gut microbial balance. This review summarizes preclinical and clinical evidence supporting the antioxidant potential of probiotics in DM management, with a focus on underlying mechanisms. Strains from the Lactobacillus and Bifidobacterium genera are the most extensively studied and have demonstrated hypoglycemic and antioxidant effects, including the enhancement of key antioxidant enzymes and reductions in lipid peroxidation and nitrosative stress markers. Probiotics have also shown beneficial effects in DM-associated complications, particularly diabetic neuropathy and nephropathy. While clinical data are still limited, recent findings underscore oxidative stress as a critical therapeutic target influenced by probiotic interventions. Overall, current evidence supports probiotics as a complementary strategy for managing DM and its complications, highlighting the need for further well-designed clinical trials exploring diverse strains, formulations, and dosing regimens.